노동조합의 고용효과 분석 - 김인경 (13407, 2013)
Using Workplace Panel Survey of 2005, 2007 and 2009 waves, this study estimates the effects of trade unions on employment and the proportion of irregular workers, short-term and part-time workers, and agent temporary and outsourced workers. While the esti